2016
DOI: 10.1371/journal.pone.0158756
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the STMN1 Transcriptional Regulatory Region Affect Promoter Activity and Fear Behavior in English Springer Spaniels

Abstract: Stathmin 1 (STMN1) is a neuronal growth-associated protein that is involved in microtubule dynamics and plays an important role in synaptic outgrowth and plasticity. Given that STMN1 affects fear behavior, we hypothesized that genetic variations in the STMN1 transcriptional regulatory region affect gene transcription activity and control fear behavior. In this study, two single nucleotide polymorphisms (SNPs), g. -327 and g. -125 , were identified in 317 English Springer Spaniels. A bioinformatics analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…We transiently transfected primary granulosa cells with these constructs as well as a control vector bearing no promoter (pGL3-Basic), and measured the luciferase activity. 0.5k-Luc showed significantly higher activity than 6.1k-Luc ( Figure 5A), which was consistent with previous studies reporting that a shorter sequence often possessed higher promoter activity in transient assay (56)(57)(58)(59).…”
Section: Lncrna-amhr2 Activation Increases Amhr2 Promoter Activity Insupporting
confidence: 92%
“…We transiently transfected primary granulosa cells with these constructs as well as a control vector bearing no promoter (pGL3-Basic), and measured the luciferase activity. 0.5k-Luc showed significantly higher activity than 6.1k-Luc ( Figure 5A), which was consistent with previous studies reporting that a shorter sequence often possessed higher promoter activity in transient assay (56)(57)(58)(59).…”
Section: Lncrna-amhr2 Activation Increases Amhr2 Promoter Activity Insupporting
confidence: 92%
“…Some animal experiments have demonstrated that Stmin1 is involved in fear processing in mice 10 , 13 , 15 and dogs. 16 However, the number of experimental studies on the association of the Stmn1 gene with anxiety and fear in humans is limited. In 2010, Broke et al 18 used the acoustic startle paradigm and a standardized laboratory protocol for the induction of fear and psychosocial stress in 113 healthy German volunteers to investigate the impact of Stmn1 gene polymorphisms (rs182455 and rs213641) on 2 fear- and anxiety-controlling effector-systems of the amygdala and found that Stmn1 genotype interacting with individuals’ gender significantly impacts fear and anxiety responses and cortisol stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a number of studies have demonstrated that Stmn1 is involved in fear processing in experimental animals. 10 , 13 , 15 , 16 For example, by constructing a single prolonged stress rat model of post-traumatic stress disorder (PTSD), Shan et al 10 found that Stmn1 in the memory loop, especially in the hippocampus, regulates MT structure through its phosphorylation at Ser25 and Ser38 and thereby participates in the mediation of fear memory abnormalities in PTSD. Using Stmn1 knockout (KO) mice, many studies have demonstrated that Stmn1 KO could lead to abnormal spike-timing-dependent long-term potentiation (LTP) and defective memory on fear conditioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have verified that stathmin1 transcription was regulated by wild type and mutant p53 [ 23 , 24 ]. Two SNPs identified in the canine stathmin1 promoter region could affect transcription factor binding [ 25 ]. MiR-34a downregulates stathmin1 by directly binding to its 3’-UTR [ 26 ].…”
Section: Discussionmentioning
confidence: 99%